The Effectiveness Of The Internal Control System Of Trade Receivables On Msme Jamu Original Java - Vinsensia Retno Widi Wisayang; Windasari Rachmawati; Abdul Karim (Soegijapranata Catholic University, 2022)
In principle, every company has one goal, which is to make a profit. Whether it's a trade industry or a service. Profit earned activities are carried out by sales activities, transactions made in cash will result in cash receipts. A credit sale will increase receivables. This makes the company's assets increase and can support the development of the company. This research method uses primary data and secondary data, where the object of this study is the original Java herbal medicine UMKM. Using the quantitative method of deskriftive and the sign test method. Based on the results of the interview conclusion with the conclusion of the theory can be known that the application of the internal control system of trade receivables in the original Java herbal medicine MSMEs is still very simple, because the medium to upper business is still small, so there are still many systems that have not been implemented. The data above shows that the test sign test value of 0.065 0.05 that H1 is accepted so there is a significant difference between internal control activities in MSMESherbal medicine asli mbak Sum before and after being given the effectiveness of the internal control system.